If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 91 = 6(12 + b) 91 = (12 * 6 + b * 6) 91 = (72 + 6b) Solving 91 = 72 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 91 + -6b = 72 + 6b + -6b Combine like terms: 6b + -6b = 0 91 + -6b = 72 + 0 91 + -6b = 72 Add '-91' to each side of the equation. 91 + -91 + -6b = 72 + -91 Combine like terms: 91 + -91 = 0 0 + -6b = 72 + -91 -6b = 72 + -91 Combine like terms: 72 + -91 = -19 -6b = -19 Divide each side by '-6'. b = 3.166666667 Simplifying b = 3.166666667
| 25-x÷2=x/3 | | 5/42x=-6/42 | | 2b-3b= | | 5/42=-6/42 | | 9x-5=7x+29 | | -5(3x-4)= | | 25c^2+20ct+4t^2=0 | | 5x+6=3x+34 | | 48v^2-120v+75=0 | | 5x+7=3x+49 | | 2x+4x+60=180 | | 100c^2-120c+36=0 | | 6x-18=-126 | | (-1/3)2 | | 5x+60+10x=180 | | 8x+3=6y-8 | | 3(y-6)-5y=-8 | | 42sqrt(4*2/41xsqrt00.125*x | | 8y/2 | | 42sqrt(4*2/41xsqrt00.125 | | 6y-2=9+10y | | 12×10^7/4×10^4 | | 34=2(v+2)-8v | | cos(34)•20/x | | 5(y-2)/4=-4y | | 3(6x-9)-8=18x-35 | | 9x+1=9(x+4) | | e^1.2x=4/x | | 2n-1=-3n+9 | | 6x^2-21x-12/3x-4 | | 32=8x+4(x+2) | | 7+x-7=12 |